VILLAGE FUND MANAGEMENT MODEL THROUGH PARTICIPATION POLICY - Sintha Dewi, Dyah Adriantini; Heniyatun; Syafingi, Habib Muhsin; Suharso (International Journal of Psychosocial Rehabilitation, 2020)
Non-autonomous utilization policy has an impact on the use of villages funds. One contributing factor is the regulations governing the technical use of funds, from planning, implementation to reporting. This research, therefore aims to formulate an effective model of village fund management to improve community welfare, with the empirical legal research method, which allows the direct interaction with the community used to obtain data. Furthermore, the purposive sampling technique was used to obtain information from Borobudur District, with the inductive method used for analysis. The results showed that the Borobudur Village Government had developed innovations in the use of funds through the mechanism of equity participation in the BUMD. This innovation was carried out by referring to Law No. 6 of 2014 concerning funds. BUMD was used due to its collective economic activity between the village government and the community. This condition is seen in the construction of a control center (Balkondes) as a means to support rural tourism, which has implications on its budgets and revenues.